Characteristics of Rumen Fluid, pH and Number of Microbia - Suarjana, I Gusti Ketut; Tono Pasek Gelgel, Ketut; Sudipa, Putu Henrywaesa (Journal of Veterinary and Animal Sciences; Vol 4 No 1 (2021), 2021)
Abstract. This research purpose is to determine the characteristics of pH rumen fluid and the amount of microbes in the rumen of Bali cattle. The research sample is healthy bali cattle rumen fluid which is slaughtered at Pesanggaran slaughterhouse Denpasar with a total of 30 samples. The research method uses conventional methods and refers to the method according to [6]. The total population of bacterial and fungal colonies was calculated by the pour plate method. Bacterial colonies were cultured on nutrient agar plates and fungi colonies were cultured on sabouraud dextrose agar plates . The Population of Enterobacteriaceae bacterial colonies was calculated by scatter method on Mac Conkey agar plate and Escherichia coli colony on Eosin Methylen Blue agar plate . Rumen liquid pH measurement is directly done with pH indicator strips. The study was conducted observationally and the data obtained were analyzed descriptively. The results showed that the total number of bacteria in the rumen fluid of Bali cattle with an average of 64x10 4 cfu/g, the number of fungal colonies with an average of 161x10 5 cfu/ g, the number of Coliform colonies was 23x10 4 cfu/g, the number of non-Coliform 28x10 3 cfu/g, E.coli 18x10 3 cfu/g and the mean The pH of Balinese cattle rumen fluid 6.9.   Keywords : Balinese Cattle Rumen Fluid, Coliform , E. Coli , Fungi,  non-Coliform, Total Bacteria , pH